2021
DOI: 10.3390/rs13071359
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Unmanned Aerial Systems (UASs) in Hydrology: A Review

Abstract: In less than two decades, UASs (unmanned aerial systems) have revolutionized the field of hydrology, bridging the gap between traditional satellite observations and ground-based measurements and allowing the limitations of manned aircraft to be overcome. With unparalleled spatial and temporal resolutions and product-tailoring possibilities, UAS are contributing to the acquisition of large volumes of data on water bodies, submerged parameters and their interactions in different hydrological contexts and in inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 174 publications
(185 reference statements)
0
30
0
3
Order By: Relevance
“…However, SfM lacks point cloud density compared to lidar and is, therefore, best utilised in combination with lidar where available [97]. Combined lidar and SfM methods can be applied to a variety of wetland studies for applications such as vegetation inventories, identifying open water extents, flood detection analysis, and topographical features [98,99]. UAV imagery has been assessed for wetland classification using pixeland object-based analyses, corroborating that object-based analysis typically yields greater accuracies.…”
Section: Unmanned Aerial Vehiclesmentioning
confidence: 90%
“…However, SfM lacks point cloud density compared to lidar and is, therefore, best utilised in combination with lidar where available [97]. Combined lidar and SfM methods can be applied to a variety of wetland studies for applications such as vegetation inventories, identifying open water extents, flood detection analysis, and topographical features [98,99]. UAV imagery has been assessed for wetland classification using pixeland object-based analyses, corroborating that object-based analysis typically yields greater accuracies.…”
Section: Unmanned Aerial Vehiclesmentioning
confidence: 90%
“…A potential solution to this tradeoff is combining LiDAR data with SfM data [61]. Combined LiDAR and SfM methods can be used not only in vegetation inventory studies, as demonstrated in this review, but also in surface water, flooding detection analysis [38], and morphological features [35].…”
Section: Geographic and Technical Characteristics Of The Reviewed Uav Applicationsmentioning
confidence: 99%
“…Other researchers have explored similar topics involving the use of UAVs in aquatic ecology, wetland identification, and hydrologic modeling [2,30,37]. Vélez-Nicolás et al [38] conducted a literature review on UAV applications in hydrology and selected 122 research papers for analysis, while Jeziorska [37] explored UAV sensors and cameras for a broad array of applications, and coupled this with a focus on 20 highlighted research papers pertaining to wetland and hydrological modeling. Mahdianpari et al [30] examined wetland classification studies from 1980-2019 across North America using a variety of remote sensing techniques, and found only four UAV-based studies, all of which took place in Florida.…”
Section: Introductionmentioning
confidence: 99%
“…However, video-imaging techniques also have limited spatial coverage since they are fixed, site-specific ground-based technologies [30]. While airborne methods and UAVs are more flexible in their potential coverage, they are also limited due to dependence on human operators, which discourages continuous observation [33], whereas understanding coastal dynamics requires continuous and fre-quent monitoring of shorelines. Consequently, long-term, uninterrupted, and updated information of shoreline displacement that is vital for coastal engineering and sustainable adaptation plans is usually scarce in many coastal areas [34].…”
Section: Shoreline Detectionmentioning
confidence: 99%